The effect of 21st century acculturation module on the students’ higher order thinking skills and academic achievement - Mohamad Mohsin, Siti Faizzatul Aqmal (2020)
This research was conducted to examine the effect of the 21st Century Acculturation Module on 21st Century Skills and academic achievement. The research sample comprised 120 form four students who took the Science subject from three secondary schools in Selangor and Perak. The experimental group consisted of students from Selangor, while the control group consisted of students from Perak. The quasiexperimental design was applied using quantitative data. Data collected were analysed using descriptive and inferential statistics, such as means, standard deviations, independent sample T-test and PLS-SEM. The result shows that for 21st Century Skills, namely Learning and Innovation (LI), the mean difference between control and experimental group was significant (t = -12.649, p = 0.000). As for the Life and Career (LC), the mean difference between control and experimental group was significant (t = -52.590, p = 0.000). In the case of Information, Media, and Technology (IMT) the mean difference between control and experimental group was significant (t = - 45.745, p = 0.000). Research finding also shows that there was a significant difference on students’ academic achievement (AA) (t = -12.700, p = 0.000) between the experimental and control groups. The result gathered from PLS-SEM indicated that the moderating role of the developed module on the relationship between LC and AA was significant. The proposed module derived from that the amalgamation of Dale’s Cone of Experiences and Revised Bloom’s Taxonomy frameworks along with the technology usage in a virtual learning environment is evident to enhance 21st century skills of the students and they also performed better in the academic achievement.